As mulheres da comunidade Cristo Rei, Benjamin Constant, AM: trabalho, renda e segurança alimentar - Araújo, Joicilene de Souza (Brasil, 2024)
Gender inequalities make it impossible for women to work in the agro-ecosystem and reinforce the reproduction of prejudice. The aim of this study was to analyse the work processes, income and food security of women in the Cristo Rei Community, Benjamin Constant, Amazonas. The study was carried out in the Cristo Rei Community, located on the island of Aramaçá in Benjamin Constant, Amazonas, the research design in terms of the proposed objectives was an exploratory study, the classification of the research is configured by the quantitative-qualitative analysis, a bibliographic survey was carried out, a meeting with a focus group, semi-structured interviews, direct observation and two recall questionnaires: a) work and b) food. Eight categories were identified: a) domestic; b) backyard; c) swidden; d) fishing; e) flour production; f) caring for children/grandchildren; g) making fishing gear and h) pluriactivity and subcategories of work. Women's work is diverse and they work long hours, which can be seen as gender inequality in family farming. Monetary income is acquired through government programmes such as Bolsa Familia, BPC (Continuous Cash Benefit) and Seguro Defeso for artisanal fishermen, as well as from agricultural and non-agricultural work. The products that form part of the residents' diet are very diverse, both those produced in the community itself and those bought in the municipal centres of Tabatinga and Benjamin Constant, although the products available from the crops are consumed most. Women take on countless roles within the family units that contribute significantly to maintaining families in the Cristo Rei Community.